2014
DOI: 10.3389/fnhum.2014.00620
|View full text |Cite
|
Sign up to set email alerts
|

Alpha band functional connectivity correlates with the performance of brain–machine interfaces to decode real and imagined movements

Abstract: Brain signals recorded from the primary motor cortex (M1) are known to serve a significant role in coding the information brain–machine interfaces (BMIs) need to perform real and imagined movements, and also to form several functional networks with motor association areas. However, whether functional networks between M1 and other brain regions, such as these motor association areas, are related to the performance of BMIs is unclear. To examine the relationship between functional connectivity and performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 101 publications
1
26
0
5
Order By: Relevance
“…Many previous studies have used invasive or non-invasive measurements to demonstrate the importance of cM1 activity for decoding movement types, directions, and trajectories during real and imagined movements 6 7 20 34 . Recently, we demonstrated the effect of functional connectivity between cM1 and motor association areas on BMI performance during real and imagined movements using MEG 31 . To the best of our knowledge, no previous studies have investigated the relationship between cM1 activity representing motor information in real and imagined movements with high spatiotemporal resolution using non-invasive measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have used invasive or non-invasive measurements to demonstrate the importance of cM1 activity for decoding movement types, directions, and trajectories during real and imagined movements 6 7 20 34 . Recently, we demonstrated the effect of functional connectivity between cM1 and motor association areas on BMI performance during real and imagined movements using MEG 31 . To the best of our knowledge, no previous studies have investigated the relationship between cM1 activity representing motor information in real and imagined movements with high spatiotemporal resolution using non-invasive measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies that used invasive 26 or non-invasive methods 27 28 29 30 also reported that imagined movements activate M1. In addition, we recently reported that the strength of functional connectivities between M1 and the motor association area affects the performance of BMIs in both real and imagined movements 31 . Furthermore, M1 activity during imagined movements has been recorded not only in healthy subjects but also in patients with stroke 21 , tetraplegia 6 7 32 , and ALS 33 .…”
mentioning
confidence: 99%
“…anxiety) or demographical items to predict BCI performance, but the associated results seem to be contradictory (55; 56; 57). Recently, FC-based metrics have been shown to correlate with the user's performance suggesting potential strategies for improving MI-based BCI accuracy (58).…”
Section: Network Predictors Of Learning Ratementioning
confidence: 99%
“…Based on this observation, we hypothesized that a treatment capable of increasing alpha-band FC between the motor cortex and the rest of the brain should have beneficial effects on motor performance. Recent studies have indeed shown that traditional neurofeedback training of SMR modulation improves motor cortex FC as a marker of recovery (Várkuti et al, 2013;Sugata et al, 2014). Here, we developed a neurofeedback system where EEG FC is trained directly (Sacchet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%